PENGARUH PRODUKSI, HARGA DAN NILAI TUKAR RUPIAH TERHADAP EKSPOR BIJI KOPI DI INDONESIA - Askia, Dhia; , Asnawi , Asnawi; Murtala; Cut Putri Mellita Sari (LPPM Universitas Malikussaleh - Indonesia, 2025)
This study aimed to investigate the influence of coffee production, international coffee prices, and the Rupiah exchange rate on Indonesia's coffee bean exports. The research utilized secondary data collected from 1990-2023. This study uses the Autoregressive Distributed Lag (ARDL) method for analysis. The research findings indicated that coffee production had a positive but not statistically significant impact on Indonesian coffee bean exports in the short run. At the same time, its effect became positive and significant in the long run. Conversely, international coffee prices demonstrated a negative and significant influence on exports in the short run, but this effect turned negative and insignificant in the long run. Finally, the Rupiah exchange rate positively and significantly impacted coffee bean exports in the short run. However, its effect shifted to negative and insignificant in the long run.